2021
DOI: 10.1002/smll.202102016
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Reversible Lithium Metal Anode by Constructing Lithiophilic Bi‐Nanosheets

Abstract: As a favorable candidate for the next‐generation anode materials, metallic lithium is faced with two crucial problems: uncontrollable lithium plating/stripping process and huge volume expansion during cycling. Herein, a 3D lithiophilic skeleton modified with nanoscale Bi sheets (Ni@Bi Foam, i.e., NBF) through one‐step facile substitution reaction is constructed. Benefiting from the nanoscale modification, smooth and dense lithiophilic Li3Bi layer is in situ formed, which improves the uniform deposition of Li s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Due to the special heterogenous interface, the GMM@Cu/Li||LFP cell exhibits obvious superiority compared to some representative anodes for LMBs (Figure 8e). [50][51][52][53][54][55][56] Impressively, the full-cell of GMM@Cu/ Li||LFP delivers an extremely stable cycle performance with high reversible capacity of 122 mAh g -1 and high capacity retention of 90% after 500 cycles at 1 C (Figure 8f). Also its polarization voltages are also very stable in long-term cycling (Figure S21, Supporting Information).…”
Section: Full-cell With Gmm@cu For Practical Applicationmentioning
confidence: 99%
“…Due to the special heterogenous interface, the GMM@Cu/Li||LFP cell exhibits obvious superiority compared to some representative anodes for LMBs (Figure 8e). [50][51][52][53][54][55][56] Impressively, the full-cell of GMM@Cu/ Li||LFP delivers an extremely stable cycle performance with high reversible capacity of 122 mAh g -1 and high capacity retention of 90% after 500 cycles at 1 C (Figure 8f). Also its polarization voltages are also very stable in long-term cycling (Figure S21, Supporting Information).…”
Section: Full-cell With Gmm@cu For Practical Applicationmentioning
confidence: 99%
“…The oxidation peak at 0.9 V versus Li + /Li is the dealloying of Li 3 Bi. , Compared with the base electrolyte, the Li deposition/stripping peaks at ∼0 V versus Li + /Li are stronger and more symmetric, indicating the elevated dynamics of Li deposition/stripping by the formation of the Li 3 Bi alloy. The Li 3 Bi layer has been considered to have lithiophilic property by its low surface energy and improves the uniform deposition of lithium ions. , …”
Section: Resultsmentioning
confidence: 99%
“…The Li 3 Bi layer has been considered to have lithiophilic property by its low surface energy and improves the uniform deposition of lithium ions. 33,34 The Li-Bi alloy layers formed by spontaneous and electrochemical reactions were tested by X-ray diffraction (XRD) measurement (Figure 1). An obvious Li 3 Bi peak at 23°c an be seen after being cycled 2, 4, and 8 h in the Bi(TFSI) 3added electrolyte, indicating the bismuth protective layer formed by the electrochemical reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…42 Recently, Liu et al constructed nanoscale Bi sheets on the 3D skeleton to obtain a highly reversible lithium metal anode owing to the formation of the lithiophilic Li 3 Bi layer. 43 To the best of our knowledge, Bi 2 O 3 nanosheets as active sitemodified carbon substrates to regulate the Li deposition behavior has not been explored, and the mechanism of the lithiophilic Bi 2 O 3 in the improvement of electrochemical performance are indeed not deeply understand.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Bismuth (Bi)-based materials have been used as a promising anode for lithium-ion batteries (LIBs) because of relatively low-cost advantage and high theoretical specific capacity according to the reversible (de) alloy reaction of Bi + 3Li + + 3e ↔ Li 3 Bi. , For example, Fang et al reported the use of Bi 2 O 3 nanoparticles encapsulated by three-dimensional porous nitrogen-doped graphene as the anode for high-rate LIBs, in which Bi 2 O 3 can be converted into metallic Bi nanoparticles (NPs) and ionic conductor Li 2 O during the initial discharge process . Recently, Liu et al constructed nanoscale Bi sheets on the 3D skeleton to obtain a highly reversible lithium metal anode owing to the formation of the lithiophilic Li 3 Bi layer . To the best of our knowledge, Bi 2 O 3 nanosheets as active site-modified carbon substrates to regulate the Li deposition behavior has not been explored, and the mechanism of the lithiophilic Bi 2 O 3 in the improvement of electrochemical performance are indeed not deeply understand.…”
Section: Introductionmentioning
confidence: 99%